Deteksi Potensi Risiko Kecurangan Laporan Keuangan Menggunakan Fraud Score Model Pada Perusahaan Perbankan Di Bursa Efek Indonesia, Periode 2015-2016 - Apriliyani, Ika Berty; Oemar, Fahmi; Indarti, Indarti (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study aims to analyze the factors that encourage fraud in the financial statements by using Fraud Diamond analysis. This study analyzes the effect of proxy variable pressures by financial stability, external pressure, financial targets, opportunities indicated by industry traits, proxy razionalization by audit opinion, and proxying capability of directors replacement to financial statement fraud by using fraud score model (F-Score).The data used is secondary data. The population in this study is a Banking company listed on the Indonesia Stock Exchange 2014-2016. Determination of sample research using purposive sampling method and data processing using multiple linear regression Factors in the Fraud score model able to prove the relationship and its effect on the tendency of financial reporting fraud such as Pressure, Opportunity, Rationalization, and Capability. This is possible because of the different characteristics of banking companies with other types of companies, where the level of regulation and controlling in different banking companies than other types of companies so that the practice of fraudulent tendency of financial statements in banking companies is still rare.